Validation of a novel cost effective easy to produce and durable in vitro model for kidney-puncture and percutaneous nephrolitholapaxy-simulation - Klein, Jan-Thorsten; Rassweiler, Jens; Rassweiler-Seyfried, Marie-Claire (Journal of endourology, 2018)
Nephrolithiasis is one of the most common diseases in urology. According to the EAU Guidelines, a percutaneous nephrolitholapaxy (PNL) is recommended when treating a kidney stone >2 cm. Nowadays, PNL is performed even for smaller stones (<1 cm) using miniaturized instruments. The most challenging part of any PNL is the puncture of the planned site. PNL-novice surgeons need to practice this step in a safe environment with an ideal training model. We developed and evaluated a new, easy to produce, in vitro model for the training of the freehand puncture of the kidney.
Gesehen am 30.10.2019